Successful Systemic Thrombolysis in a Neonatal Occlusive Abdominal Aortic Thrombus Secondary to Hypernatremic Dehydration: A Case Report and Literature Review. Issue 7 (October 2020) - Al Nuaimi, Mohammed; Williams, Suzan
Abstract : A 6-day-old neonate presented with hypernatremic dehydration and weight loss. Fluids were started for rehydration. He was subsequently found to have signs of reduced lower limb perfusion and investigations revealed an abdominal aortic thrombus and bilateral occlusion of renal arteries. Systemic thrombolysis led to complete resolution of renal artery thrombi with no major complications. A review of similar cases with hypernatremic dehydration and thrombosis is provided.